Methods of carotid endarterectomy - A. N. Kazantsev; R. A. Vinogradov; K. P. Chernykh; M. O. Dzhanelidze; G. Sh. Bagdavadze; S. V. Artyukhov; A. E. Chikin; Yu. P. Linets (Российский кардиологический журнал)
This literature review is devoted to various carotid endarterectomy (CE) methods that exist today in Russia. The pros and cons of conventional and eversion technique of the operation are given. It is indicated that the former is associated with higher long-term rate of restenosis, aneurysm and patch infection. The second is associated with higher prevalence of intraoperative internal carotid artery (ICA) thrombosis due to intimal detachment distal to endarterectomy area. The following CE methods for patients with prolonged ICA involvement are described: neo bifurcation formation, autoarterial reconstruction, ICA autotransplantation, plastic using an occipital artery flap. The methods of CE with carotid body saving have been demonstrated: 1. Swallow tail type patch repair proposed by R.I. Izhbuldin; 2. S-shaped arteriotomy proposed by K. A. Antsupov; 3. Two types of operations proposed by R. А. Vinogradov; 4. Сutting off the ICA with sections of common and external carotid artery proposed by A. N. Kazantsev; 5. Glomus-saving ICA autotransplantation in patients with prolonged atherosclerotic involvement. The role of ICA transposition over the hypoglossal nerve in eversion CE is presented. The glomus-saving CE with ICA transposition, called Chik-Chirik CE, is described. Conclusions are drawn on the need to demonstrate all CE types in the novel Russian guidelines for the management of patients with of head and neck arterial diseases.